An Analysis of Teacher Speech Act in Giving Motivation for English Students - Muhammad Azizul Chakim; Haris Dibdyaningsih (Journal of English Language Teaching and Islamic Integration, 2019)
Speaking is defined as a reflection of the students’ ability to communicate  in  English.  Compared  to  the  other  language  skills, speaking  is  considered  to  be  more  difficult  because  it occurs  in  real time, and when we speak we cannot edit and revise what we want to say,  as  we  can  do  in  writing.  Speaking  skill  was  considered  as  a difficult  skill  to  be  maintained;  therefore,  an  extensive  practice  is required  to  perform.  However,  students  tend  to  be  silent  in  the classroom  since  they  lack  of  self-confidence.  Students  need  more practice, so that they could learn to express their feeling, thought, idea, emotion  and  intention,  whereas,  teachers  should  create  a  good situation in teaching learning process in the classroom. Gallery walk is one  of  the  most  learner  centered  activities  which  provides  good situation  in  teaching  learning  process.  It  is  a  presentation  method  in which individual learners or groups displayed their products, and they walked  around  the  room  viewing  others’  work.  The  purpose  of  this paper is to describe gallery walk technique to teach speaking in Senior High  School.  This  technique  seems  to  be  suitable  to  provide  fresh atmosphere in teaching English especially in Speaking.